Analysis of Service Quality for BPJS Health Participants: A Case Study of a Private Hospital in Bandung - Dwikora Harjo; Diana Prihadini; Jeruth Ngonzi Tinka; Mara Elaiza Augustine Flores; Alian Natision (Ilomata International Journal of Social Science, 2022)
Hospitals as one of the health care facilities in general have a very important role in efforts to improve the health status of the Indonesian people. Increasing public awareness about health results in greater demands for improving health services. This study aims at answering the question of how the service is perceived by BPJS health participants at a private hospital in Bandung and what aspects were complained by the BPJS participants. This is a qualitative research with a case study approach. Data was collected by means of semi-structured interviews with 20 BPJS health users. The results of this study indicate that of the 14 elements of service principles, the principle of justice in obtaining services is the element that receives the most complaints. Complaints are addressed not only to service officers but also to medical personnel. Therefore, it is important for hospitals to improve the quality of service by paying attention to the elements of justice for each patient.